Change in Putin's Russia : power, money and people - Pirani, Simon, 1957- (Pluto Press, 2010)
Simon Pirani investigates the interaction of power, money and people in Russia during the presidencies of Vladimir Putin and his successor Dmitry Medvedev. Profiling the Putin team, including contingents from the security services and pro-market economic "reformers," Pirani argues that the economic growth it presided over during the oil boom was one-sided. The gap between rich and poor widened. Now the boom is over, inequalities will multiply further. As well as explaining Russia's economic trajectory, the book provides a unique account of the social movements that are working against an increasingly authoritarian government to change Russia for the better. This is the perfect introduction for undergraduates approaching Russia for the first time and those who wish to know how Russia will change during the economic crisis